The Communication Strategy in Conveying Effective and Efficient Message Construction in Tourism Industry - Lestari, Ayu; Sunra, La; Abdullah, Abdullah (ELITERATE : Journal of English Linguistics and Literature Studies, 2023)
Tourism is one of the domestic industries that has the fastest growing aspect in the world and is also a major foreign exchange earner, as well as job creation for many countries. It is one of the most remarkable economic and social phenomena. Tourism can be defined as the movement of people from another place (with the intention of returning) or a visit to a place that has a unique or beautiful destination and is worth visiting for a minimum period of twenty-four hours, up to a maximum of six months for reaction and pleasure purposes only. In developing tourism certainly requires an effective and efficient form of delivering messages to consumers and other organizations, therefore tourism requires a communication strategy in conveying messages that are effective and efficient. This study aims to analyze what communication strategies the tourism industry uses in conveying messages to brochures they have made. The research method that the researchers used in this study was a qualitative research method and a qualitative descriptive method. Researchers analyzed this research with depth-interviews, observation and literature studies. This study has 2 problems in it, the first problem proves that the tourism industry uses these 3 theories to form an effective and efficient communication in conveying messages on Brochures. And the second problem, there are 3 strategies that show how the tourism industry overcomes the ineffectiveness and inefficiency of delivery in the Brochure, so that the Brochure can be effective and efficient and can be understood by readers.Key words: Tourism Industry, Communication Strategy, Effective and Efficient.